First-in-child use of the oral selective prostacyclin IP receptor agonist selexipag in pulmonary arterial hypertension. (May 2017) - Geerdink, Lianne M.; Bertram, Harald; Hansmann, Georg
Pulmonary arterial hypertension (PAH) is a complex disease with a poor prognosis. Selexipag is a selective prostacyclin receptor agonist with vasodilatory, anti-proliferative, anti-inflammatory, and pro-angiogenic properties. However, no clinical data on its therapeutic use in children with PAH are currently available. Here, we report the case of a 12-year-old girl who presented in World Health Organization (WHO) functional class III and right ventricular (RV) failure with recurrent syncope, dizziness, and progressive fatigue for two years. Cardiac catheterization revealed severe precapillary PAH: mean right atrial pressure (RAP) = 10–13 mmHg, right ventricular end-diastolic pressure (RVEDP) = 13 mmHg, left ventricular end-diastolic pressure (LVEDP) = 7 mmHg, mean pulmonary arterial pressure (PAP) = 81 mmHg, and mean aorta ascendens pressure = 89 mmHg. The pulmonary vascular resistance index (PVRi) was 25.2 WU × m 2 . An oral combination therapy was started with a phosphodiesterase type 5 inhibitor (sildenafil 3 × 20 mg) and an endothelin-1 receptor antagonist (bosentan 2 × 62.5 mg). No significant clinical/hemodynamic improvement was seen after nine months of dual therapy, so that the patient was transferred to our institution. We agreed upon the off-label add-on use of oral selexipag. Within ten days, we up-titrated selexipag to a final (max. adult) dose of 1600 mcg twice daily. After six months, the patient had: (1) decrease in PVR index, pulmonary artery acceleration time, RAP, RVEDP, right atrial/RV size; (2) re-gain of vasoreactivity; and (3) improvement of cardiac index, 6-minute walking distance, functional class, body weight, and CAMPHOR score. Our encouraging results suggest the consideration of off-label use of oral selexipag in children with severe PAH, preferably in a protocol-driven prospective study.